Bronze-type vanadium dioxide holey nanobelts as high performing cathode material for aqueous aluminium-ion battery - Cai, Yi (2021)
Aqueous rechargeable aluminium-ion batteries (AIBs) are promising post lithium-ion battery candidates. However, the capacity and cycling stability are limited by the cathode materials, hindering their widespread application. Herein, bronze-type vanadium dioxide (VO2–B) holey nanobelts have been designed as the cathode material to improve both the capacity and cycling stability for high-performance aqueous AIBs. Benefiting from the unique shear structure and two-dimensional holey nanobelt morphology, the VO2–B electrode delivers a superior specific capacity of up to 234 mA h g−1 at 150 mA g−1 and exhibits a high capacity retention of 77.2% over 1000 cycles at 1 A g−1, which are among the best cathode performances reported for aqueous AIBs. Moreover, a combination of electro-kinetic analysis and ex situ structural evolution characterization experiments reveals the reaction storage mechanism underlying the superior performance. Specifically, proton and Al3+ ions can reversibly co-intercalate/de-intercalate into/from VO2–B. The integration of shear structure and unique holey nanobelts may open the route to the design of high-performance cathodes for multi-valence ion batteries.